Sustainable development and the arts. (2012) - Shrivastava, Paul; Ivanaj, Vera; Ivanaj, Silvester
The sustainability discourse has largely played out in the domains of natural sciences and technology, with recent contributions from the social and political sciences. These contributions have been significant and our understanding of sustainability challenges has improved greatly over the past three decades. However, our individual, organisational and collective actions have lagged behind and the actual problems of sustainability have become worse in the same period. In this paper we argue that we can get better action and behavioural commitments to sustainability by using the arts, art-based methods, and aesthetics to develop passion and emotional connection for sustainable organising and living.